Genetic parameters of some carcass and meat quality traits in Betong chicken (KU line) - Bungsrisawat, Panatda; Tumwasorn, Sornthep; Loongyai, Wiriya; Nakthong, Sasitorn; Sopannarath, Panwadee (Agriculture and Natural Resources, 2018)
Carcass and meat quality are important traits in poultry production. A breeding plan which emphasizes these traits should be considered to increase production. The objectives of this study were to estimate heritability and genetic correlations of some carcass and meat quality traits and to compare multipletrait animal models with zero (Zero Model) and non zero (Non-zero Model) additive genetic covariances among traits in Betong chicken (KU line). Pedigree information and performance data of the Betong chicken (KU line) population were used to estimate variance components and genetic parameters using multiple-trait animal models. Two models were employed in this study, where fixed effects were classified as hatching batch and sex. The random effects were assumed to be additive genetic and residual effects. From the Non-zero Model, heritability estimates of body weight at age 16 wk (BW16) and breast meat weight (BMW) were 0.47 and 0.58, respectively. Heritability estimates of meat quality traits ranged from 0.15 to 0.33 with large standard errors. Genetic and phenotypic correlations between BW16 and BMW were high and positive (0.63 and 0.68, respectively). Genetic correlations among meat quality traits had large standard errors. BW16 and BMW may not be associated with meat quality traits. These results indicated that BW16 and BMW can be improved using genetic selection as a criterion in this population. Selection emphasizing increased BW16 and BMW may not have any adverse effect on the other meat quality traits in Betong chicken (KU line).